Study guides

☆☆

Q: Who can factor 3x squared minus 2x?

Write your answer...

Submit

Related questions

(x + 3)(3x - 2)

(x - 2)(2x + 7)

(3x + 2)(2x - 3)

It is: (2x+3)(3x-8) when factored

(2x + 1)(3x - 4)

3x squared minus 25x minus 28

The factors are -1(2x + 1)(3x + 4)

It is: (3x+4)(2x-3) when factored

6x3 + 9x2 - 2x2 - 3x Before any grouping, take out the common factor, x, to give x*(6x2 + 9x - 2x - 3) = x*[3x*(2x + 3) - 1*(2x + 3)] = x*(2x + 3)*(3x - 1)

3x(6x - 1)

(x-3)(3x+1)

(x + 1)(x - 3)

(3x + 8)(3x - 8)

6x2 + 10x = 2x*(3x + 5)

3x 2 + 2x - 5 = (x - 1)(3x + 5).

3x(2x + 1)

5x3 - 3x2 + 2x = x*(5x2 - 3x + 2) The quadratic has no real factors.

(3x + 1)(x - 5)

(x + 1)(2x - 5)

2(2x-11)(3x+5)

3(3x + 2)(3x - 2)

(x - 1)(3x + 5)

2x - 3x = -x

3x squared - x squared = 2x squared

3x2-x-2 = (3x+2)(x-1)